2010
DOI: 10.1073/pnas.0915003107
|View full text |Cite
|
Sign up to set email alerts
|

Genetic flexibility of regulatory networks

Abstract: Gene regulatory networks are based on simple building blocks such as promoters, transcription factors (TFs) and their binding sites on DNA. But how diverse are the functions that can be obtained by different arrangements of promoters and TF binding sites? In this work we constructed synthetic regulatory regions using promoter elements and binding sites of two noninteracting TFs, each sensing a single environmental input signal. We show that simply by combining these three kinds of elements, we can obtain 11 of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 44 publications
0
59
0
Order By: Relevance
“…Engineering signal propagation cascades in biological systems thus requires that any given upstream input to one of the nodes results in an output that can be understood by the next node of the signal progression chain. The chances of designing biological circuits with the same ease as electronic counterparts depends on the availability of (naturally occurring or artificial) connectable logic gates, a currently fertile field of research [52,59,108]. As discussed elsewhere [19], such approaches stemming from contemporary systems and synthetic biology offer a second opportunity for attempting the design of microorganisms for environmental release as vectors of biodegradative activities for bioremediation and sensing, to reprogram effectively and efficiently microorganisms for the productionà la carte of bulk and high-added-value chemicals, and to design intervention strategies for medical applications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Engineering signal propagation cascades in biological systems thus requires that any given upstream input to one of the nodes results in an output that can be understood by the next node of the signal progression chain. The chances of designing biological circuits with the same ease as electronic counterparts depends on the availability of (naturally occurring or artificial) connectable logic gates, a currently fertile field of research [52,59,108]. As discussed elsewhere [19], such approaches stemming from contemporary systems and synthetic biology offer a second opportunity for attempting the design of microorganisms for environmental release as vectors of biodegradative activities for bioremediation and sensing, to reprogram effectively and efficiently microorganisms for the productionà la carte of bulk and high-added-value chemicals, and to design intervention strategies for medical applications.…”
Section: Discussionmentioning
confidence: 99%
“…But one can also leave behind such a rational design and adopt combinatorial procedures to explore the entire logic space of given TFs. For instance, after shuffling cis-regulatory elements of the gal circuit, the authors of [59] were able to generate 11 out of the possible 16 logic gates responsive to two inputs. The bonus of promoter shuffling is that the experimental setup scans the entire combinatorial landscape of cis-regulatory sequences, thereby accessing solutions to simple computation traps which may not be easy to figure out by rational design.…”
Section: Translating Biological Network Into Logic Circuitsmentioning
confidence: 99%
“…a AND NOT b (on AND NOT off). This idea was later expanded on to demonstrate that various combinations of synthetic promoters could combine to generate 12 out of 16 boolean logic terms (Hunziker et al, 2010). Most interestingly the results from these studies demonstrated that if a promoter does not follow a specific logic it is more likely to be leaky, in that it will drive gene expression under conditions where it is not expected to.…”
Section: Development Of Synthetic Promoters: a Historical Perspectivementioning
confidence: 94%
“…The amplified regulatory regions were the following: spf (4047775-4047954), galR (2974441-2974680), galP (3086041-3086297), the galETKM operon (791519 to 791214), galS (2239921 to 2239711), and the mglBAC operon (2238720 to 2238439). We used a promoter that is not regulated by cAMP-CRP or GalR as a control (GenBank TM accession number GQ872202) (23). pSEM2027 derivatives containing the cloned regulatory regions were digested with BamHI and used as a template for PCR amplification.…”
Section: Methodsmentioning
confidence: 99%